2010
DOI: 10.3166/ga.23.101-111
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Risk Intensity Assessment. Application to Carbonate Aquifers of the Western Mediterranean (Southern Spain)

Abstract: In this work, the groundwater contamination risk is evaluated as a measure of protection for groundwater bodies intended for human consumption. For this purpose, intrinsic vulnerability maps and hazard maps of anthropogenic activities in the studied region have been taken into account. This region is constituted by carbonate aquifers that supply water to various populations. The methodology employed to determine the contamination risk was adapted from the COST Action 620 which was developed with the aim of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…The reduction factor (Rf = 0 to 1) is used to evaluate the likelihood of contamination. Rf is always set at the highest value (1) unless any measures to reduce contaminant discharge into the environment exist [11]. In the event of contamination, Rf < 1 minimizes the risk value.…”
Section: Table 4 Scores and Classes Of Overlying Layers (O) As A Fact...mentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction factor (Rf = 0 to 1) is used to evaluate the likelihood of contamination. Rf is always set at the highest value (1) unless any measures to reduce contaminant discharge into the environment exist [11]. In the event of contamination, Rf < 1 minimizes the risk value.…”
Section: Table 4 Scores and Classes Of Overlying Layers (O) As A Fact...mentioning
confidence: 99%
“…Field survey found that these industries repurpose or process the by-products and residues into animal feed and have industrial wastewater treatment plants, which were used as the basis for Rf selection. Furthermore, livestock and agricultural activities also generate contaminants that can harm groundwater quality [11]. Primary sources include paddy fields with no measures to reduce pollution (Rf = 1), which can be differentiated into irrigated rice fields (Qn = 1.2), rainfed rice fields (Qn = 1), and dryland farms (Qn = 0.8).…”
Section: Groundwater Contamination Hazardmentioning
confidence: 99%
“…The conceptual framework in groundwater vulnerability assessment is necessary to characterize the safe and unsafe zones in groundwater resources for proper management and monitoring of groundwater with safety according to requirements of the Water Framework Directive (Jiménez-Madrid et al 2010). One of the approaches for vulnerability evaluations is the AVI ( Van Stempvoort et al 1992).…”
Section: Theoretical Conceptmentioning
confidence: 99%
“…Specific approaches, such as the COP (C: Concentration of flow; O: Overlying layers above water table; P: precipitation) method [10], have been developed specifically to assess groundwater vulnerability in carbonate (karstic) aquifers. The COP method has been extensively applied in different research studies to this type of aquifer [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%